2020
DOI: 10.1057/s41260-019-00147-z
|View full text |Cite
|
Sign up to set email alerts
|

Herds on green meadows: the decarbonization of institutional portfolios

Abstract: We analyze an emerging sustainable trend in asset management: the decarbonization of institutional portfolios. By using broad institutional ownership data, we show that investors exhibit herding behavior in the sense of decarbonization. They are inclined to follow their own or other investors' buys in green stocks and sales in brown stocks over adjacent quarters. Beyond that, we find that Hedge Funds as well as Investment Advisors lead the herd by executing trades in the sense of decarbonization. This is in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…In addition to screening mechanisms aimed at excluding carbon‐intensive companies, investors could also engage in trading in the sense of decarbonization, therefore selling carbon‐intensive and buying non carbon‐intensive firms. Benz, Jacob, Paulus, and Wilkens (2020) even show that trading in the sense of decarbonization triggers follow‐up trades by other investors, which represents herding behavior. The increasing interest of investors in sustainable investment opportunities leads consequently to a growing number of green investment vehicles that seek to incorporate not only financial but also social and environmental aspects in their investment process.…”
Section: Background and Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to screening mechanisms aimed at excluding carbon‐intensive companies, investors could also engage in trading in the sense of decarbonization, therefore selling carbon‐intensive and buying non carbon‐intensive firms. Benz, Jacob, Paulus, and Wilkens (2020) even show that trading in the sense of decarbonization triggers follow‐up trades by other investors, which represents herding behavior. The increasing interest of investors in sustainable investment opportunities leads consequently to a growing number of green investment vehicles that seek to incorporate not only financial but also social and environmental aspects in their investment process.…”
Section: Background and Related Literaturementioning
confidence: 99%
“…In this respect, we hope that this study encourages future research to further investigate the effects of ownership structure on the development of corporate CO 2 emissions. Another suggestion for future work is to examine whether the general tendency towards portfolio decarbonization (see also, e.g., Benz et al, 2020) will lead to a reaction of corporate management in terms of a CO 2 ‐efficient redesign of business processes.…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%
“…The review of the literature leads to the second contribution of this study, the investigation of herding behavior on ESG stocks. The current advanced demand for ESG assets might lead investors and fund managers to herd behavior (Przychodzen et al 2016 ; Benz et al 2020 ; Rubbaniy et al 2021 ). Most of the time inexperienced investors follow the investment behavior of others who are believed to be “market experts”.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Przychodzen et al ( 2016 ) investigate the behavior, motives and characteristics of mutual fund managers who incorporate ESG strategies into their investment decisions by providing evidence of herding behavior. In their study, Benz et al ( 2020 ) analyze institutional ownership data and conclude that investors, portfolio advisors and hedge funds follow herding behavior when decarbonizing their portfolios. Furthermore, they concluded that Institutional investors (mutual funds and hedge funds) follow ESG herding due to anxiety to accomplish the market return consensus by imitating their peer’s investment strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The initiative then proceeds to the implementation of the solutions and closes the loop with the impact evaluation. While there are abundant studies conducted regarding the implementation phase of the sustainability efforts (for example, Orazalin and Mahmood [2021]) and the in uence of the nancial market on the attitude of rms towards climate change risks (for example, Benz et al [2020]), these studies focus on the implementation of a rm's climate change related actions by skipping the primary task of identifying them.…”
Section: Introductionmentioning
confidence: 99%